RASIO-RASIO KEUANGAN DAN RETURN SAHAM - Suandewi, I Gusti Agung Ayu Siska; Sudana, I Putu (E-Jurnal Akuntansi, 2016)
This study aims to demonstrate empirically the effects of the financial ratios that liquidity ratios, activity ratios, profitability ratios and the leverage ratio on stock returns textile and garment industry in Indonesia Stock Exchange. The research sample was determined by census method by 15 issuers included in the textile and garment industry in Indonesia Stock Exchange with the observation period of five years from 2010 to 2014. Data were analyzed using classical assumption test, multiple linear regression analysis, analysis of determination, test feasibility model (F test) and test hypotheses (t test). The results of this study are as follows: the liquidity ratio has no effect on stock returns. The ratio of activity has no effect on stock returns. Profitability ratios positive effect on stock return of the textile and garment industry in Indonesia. The leverage ratio positive effect on stock return.
Keywords: stock return, financial ratios